Proton Switch in the Secondary Coordination Sphere to Control Catalytic Events at the Metal Center: Biomimetic Oxo Transfer Chemistry of Nickel Amidate Complex. Issue 14 (5th February 2021) - Kim, Soohyung; Jeong, Ha Young; Kim, Seonghan; Kim, Hongsik; Lee, Sojeong; Cho, Jaeheung; Kim, Cheal; Lee, Dongwhan
Abstract: High‐valent metal‐oxo species are key intermediates for the oxygen atom transfer step in the catalytic cycles of many metalloenzymes. While the redox‐active metal centers of such enzymes are typically supported by anionic amino acid side chains or porphyrin rings, peptide backbones might function as strong electron‐donating ligands to stabilize high oxidation states. To test the feasibility of this idea in synthetic settings, we have prepared a nickel(II) complex of new amido multidentate ligand. The mononuclear nickel complex of this N5 ligand catalyzes epoxidation reactions of a wide range of olefins by using mCPBA as a terminal oxidant. Notably, a remarkably high catalytic efficiency and selectivity were observed for terminal olefin substrates. We found that protonation of the secondary coordination sphere serves as the entry point to the catalytic cycle, in which high‐valent nickel species is subsequently formed to carry out oxo‐transfer reactions. A conceptually parallel process might allow metalloenzymes to control the catalytic cycle in the primary coordination sphere by using proton switch in the secondary coordination sphere. Abstract : "Proton‐switchable" biomimetic metal complex: An oxo‐transfer reaction at the metal center is controlled by protonation of the remote ligand sphere, which modulates electron donor ability of the ligand, promotes oxidant binding, and facilitates access to high‐valent catalytic intermediates.